An NIR Discrete Metallacycle Constructed from Perylene Bisimide and Tetraphenylethylene Fluorophores for Imaging‐Guided Cancer Radio‐Chemotherapy. Issue 7 (9th January 2022) - Ding, Yuan; Tong, Zongrui; Jin, Lulu; Ye, Binglin; Zhou, Jiong; Sun, Zhongquan; Yang, Huang; Hong, Liangjie; Huang, Feihe; Wang, Weilin; Mao, Zhengwei
Abstract: To promote the clinical theranostic performances of platinum‐based anticancer drugs, imaging capability is urgently desired, and their chemotherapeutic efficacy needs to be upgraded. Herein, a theranostic metallacycle (M ) is developed for imaging‐guided cancer radio‐chemotherapy using perylene bisimide fluorophore (PPy ) and tetraphenylethylene‐based di‐Pt(II) organometallic precursor (TPE‐Pt ) as building blocks. The formation of this discrete supramolecular coordination complex facilitates the encapsulation of M by a glutathione (GSH)‐responsive amphiphilic block copolymer to prepare M ‐loaded nanoparticles (MNPs). TPE‐Pt acts as a chemotherapeutic drug and also an excellent radiosensitizer, thus incorporating radiotherapy into the nanomedicine to accelerate the therapeutic efficacy and overcome drug resistance. The NIR‐emission of PPy is employed to detect the intracellular delivery and tissue distribution of MNPs in real time. In vitro and in vivo investigations demonstrate the excellent anticancer efficacy combining chemotherapy and radiotherapy; the administration of this nanomedicine effectively inhibits the tumor growth and greatly extends the survival rate of cisplatin‐resistant A2780CIS‐tumor‐bearing mice. Guided by in vivo fluorescence imaging, radio‐chemotherapy is precisely carried out, which facilitates boosting of the therapeutic outcomes and minimizing undesired side effects. The success of this theranostic system brings new hope to supramolecular nanomedicines for their potential clinical translations. Abstract : A theranostic metallacycle (M ) is developed for imaging‐guided cancer radio‐chemotherapy using perylene bisimide fluorophore (PPy ) and tetraphenylethylene‐based di‐Pt(II) organometallic precursor (TPE‐Pt ) as building blocks. Guided by in vivo fluorescence imaging, radio‐chemotherapy is precisely carried out, which facilitates boosting the therapeutic outcomes and minimizing undesired side effects.